2016
DOI: 10.1016/j.jval.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Differences In Pricing Policies For Generic And Biosimilar Medicines

Abstract: of the simulation, the mean number of QALYs accumulated by patients was 3.05 in the treatment arm compared to 2.56 in the natural history arm over the five year time horizon. ConClusions: Real world data may be used to monitor the cost-effectiveness of on-market drugs and to regularly refine their prices based on the value delivered in clinical practice. Performance-based pricing could be used to negotiate earlier market access for pharmaceuticals in advance of mature data on cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We also identified an abstract (Vogler et al, 2016 ) presenting the results of a survey analyzing the possible differences between pricing policies for generics and for biosimilar medicines in European countries including 25 EU countries (all except Ireland, Italy, and Luxembourg) as well as Albania, Belarus, Iceland, Norway, Serbia, Russia, Turkey, and Ukraine. While 23 of the 33 countries set the price of the generic in relation to the price of the originator, only 13 countries reported to do so for biosimilar medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified an abstract (Vogler et al, 2016 ) presenting the results of a survey analyzing the possible differences between pricing policies for generics and for biosimilar medicines in European countries including 25 EU countries (all except Ireland, Italy, and Luxembourg) as well as Albania, Belarus, Iceland, Norway, Serbia, Russia, Turkey, and Ukraine. While 23 of the 33 countries set the price of the generic in relation to the price of the originator, only 13 countries reported to do so for biosimilar medicines.…”
Section: Discussionmentioning
confidence: 99%
“…The Netherlands have been tendering for generics in the outpatient sector during the last decade, but biosimilars have been included in tenders only recently. The authors concluded that European countries tend to apply similar pricing policies for generic and biosimilar medicines (Vogler et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The review of literature data shows that the differences between the price of biosimilars and their reference biologic product ranges between 15% and 30%. On the other hand, the difference for generics and originator drugs may be up to 80% [87,88]. A systematic review that was carried out by Tuna et al to identify price difference between biotechnological reference products and biosimilars revealed that the variation differs across European countries between 0.51% and −38%.…”
Section: Critical Challenges Of Biologics and Biosimilarsmentioning
confidence: 99%
“…According to literature data the differences between the price of biosimilars and their RBP is between 15 and 30%. Whereas this difference for generics and originator drugs may be up to 80% ( Declerck and Simoens, 2012 ; Vogler et al, 2016 ). Haustein et al (2012) concluded that the use of biosimilars could significantly decrease the healthcare expenditure on biological medicines in EU national markets (2007–2020) of France, Germany, Italy, Poland, Romania, Spain, Sweden, and United Kingdom.…”
Section: Discussionmentioning
confidence: 99%